Effective employee orientation - Jerris, Linda A. (New York : AMACOM, 1993)
A concise guide to creating a benefits-driven employee orientation programme. Written for human resources managers and supervisors, as well as small-business owners, it can be used to start a program from scratch, or to try to breath new life into an outdated one.
Part 1. To what and why of orientation -- Part 2. Designing and conducting your program -- Part 3.Orientation as an ongoing activity
Keywords: EMPLOYEE ORIENTATION